Solid state fermentation of cassava peel with trichoderma viride (ATCC 36316) for protein enrishment. (2013)
"Solid state fermentation of cassava peel with emphasis on protein enrichment using Trichoderma viride was evaluated. The effect of five variables: moisture content, pH, particle size (p), nitrogen source and incubation temperature; on the true protein and total sugars of cassava peel was investigated. The optimum fermentation period was established to be 8 days. Total sugars were 5-fold higher at pH 6 relative to pH 4 and 7-fold higher when cassava peels were fermented at 30o C relative to 25 o C as well as using ammonium sulfate as the nitrogen source relative to urea or a combination of both. Total sugars ranged between 123.21mg/g at 50% initial moisture content to 374mg/g at 60% and from 190.59mg/g with particle size range of 2.00>p>1.41mm to 310.10mg/g with 4.00>p>3.35mm.True protein ranged from 229.70 mg/g at pH 4 to 284.05 mg/g at pH 6; from 200.87 mg /g with urea as nitrogen source and to 254.50mg/g with ammonium sulfate; from 213.82mg/g at 50% initial moisture content to 254.5 0mg/g at 60% moisture content, from 205.75mg/g in cassava peel with 5.6>p> 4.75mm to 268.30 in cassava peel with particle size 4.00>p>3.35mm, from 207.57mg/g at 25oC to 254.50mg/g at 30oC Cassava peel with particle size 4.00>p>3.35 mm and initial moisture content of 60% at pH 6.0, 30oC incubation temperature with ammonium sulfate (10g N / kg substrate) was most suitable for protein enrichment with Trichoderma viride. Crude protein increased from 4.21 % in unfermented cassava peel samples to 10.43 % in fermented samples. "